Bioorthogonal Labeling of Human Prostate Cancer Tissue Slice Cultures for Glycoproteomics. Issue 31 (26th June 2017) - Spiciarich, David R.; Nolley, Rosalie; Maund, Sophia L.; Purcell, Sean C.; Herschel, Jason; Iavarone, Anthony T.; Peehl, Donna M.; Bertozzi, Carolyn R.
Abstract: Sialylated glycans are found at elevated levels in many types of cancer and have been implicated in disease progression. However, the specific glycoproteins that contribute to the cancer cell‐surface sialylation are not well characterized, specifically in bona fide human disease tissue. Metabolic and bioorthogonal labeling methods have previously enabled the enrichment and identification of sialoglycoproteins from cultured cells and model organisms. Herein, we report the first application of this glycoproteomic platform to human tissues cultured ex vivo. Both normal and cancerous prostate tissues were sliced and cultured in the presence of the azide‐functionalized sialic acid biosynthetic precursor Ac4 ManNAz. The compound was metabolized to the azidosialic acid and incorporated into cell surface and secreted sialoglycoproteins. Chemical biotinylation followed by enrichment and mass spectrometry led to the identification of glycoproteins that were found at elevated levels or uniquely in cancerous prostate tissue. This work therefore extends the use of bioorthogonal labeling strategies to problems of clinical relevance. Abstract : Glycoprotein in a haystack : The metabolic labeling of human prostate cancer tissue slice cultures was employed to introduce azide‐labeled sialic acid into cell‐surface and secreted glycoproteins. Chemical biotinylation followed by enrichment and mass spectrometry led to the identification of glycoproteins that were found at elevated levels or uniquely in cancerous prostate tissue.